A retrospective administrative database analysis of the association between clonorchiasis or helminthiasis and the development of cholelithiasis. (4th March 2019) - Chen, Chien-Hua; Lin, Cheng-Li; Hsu, Chung Y.; Kao, Chia-Hung
Abstract: Purpose: Parasite infestation (PI) is reportedly related to intrahepatic stones (IHSs) and common bile duct (CBD) stones. This study assessed the association of clonorchiasis and helminthiasis with the sub-types of cholelithiasis. Methods: The study cohort consisted of 713 patients who were aged ≥20 years with clonorchiasis or helminthiasis for the first time between 2000 and 2010 from the National Health Insurance Research Database. The controls without clonorchiasis and helminthiasis were randomly selected with a 1:1 propensity score matching. All patients were followed up until the end of 2011 to measure the incidence of cholelithiasis. Results: The risks of cholelithiasis in the clonorchiasis (adjusted hazard ratio [aHR] = 3.72, 95% confidence interval [CI] = 2.01–6.90) and helminthiasis (aHR = 2.27, 95% CI = 1.25–4.16) were higher than in the non-PI cohort. Patients with clonorchiasis had increased risks of gallstones without bile duct stones (aHR = 3.13, 95% CI = 1.54–6.39) and bile duct stones without gallstones (aHR = 4.75, 95% CI = 1.23–18.4). Patients with helminthiasis had an increased risk of gallstones without bile duct stones (aHR = 2.20, 95% CI = 1.11–4.33), but no higher risk of bile duct stones without gallstones was observed in helminthiasis (aHR = 2.22, 95% CI = 0.54–9.06), despite its high aHR. Neither clonorchiasis nor helminthiasis had an increased risk of concomitant gallstones and bile duct stones. Conclusion: Clonorchiasis is related to the development of not only gallstones, but also bile duct stones, and helminthiasis is only associated with the development of gallstones. However, cases of PI are rare in Taiwan, and this requires more international studies to clarify the association between helminthiasis and bile duct stones.